A novel controlled release ethanol emitter: preparation and effect on some postharvest quality parameters of Chinese bayberry during storage. (18th May 2017) - Mu, Honglei; Gao, Haiyan; Chen, Hangjun; Fang, Xiangjun; Han, Qiang
Abstract: BACKGROUND: Reducing spoilage and prolonging the shelf‐life of food materials are both critically important in the food industry. Among the many available preservatives, ethanol has been widely used for the storage of fruits and vegetables. Although a few ethanol emitters are available in the form of antimicrobial packaging, these ethanol emitters demonstrate high volatility, uncontrolled release and other disadvantages, and so the practical applications are limited. RESULTS: A novel ethanol gel with a controlled release rate was prepared by a gelatification reaction between ethanol and sodium stearate to overcome the disadvantage of conventional ethanol emitters. The hardness, adhesiveness and cohesiveness of developed ethanol gels increased, whereas the springiness decreased along with an increase in the sodium stearate concentration. The release rate of ethanol in the gels was controlled by the concentration of sodium stearate, in which a first‐order release kinetic was observed. The release rate constant ( k ) of the gels with 12.5, 37.5, 62.5 g kg −1 of sodium stearate was 0.58 ± 0.029, 0.49 ± 0.035 and 0.41 ± 0.021 h −1, respectively, at 25 °C. The application of the controlled release ethanol emitter with respect to the storage of Chinese bayberry fruit demonstrated its ability to reduce the decay rate, maintain firmness and inhibit increased malondialdehyde content at 4 °C. CONCLUSION: In terms of practical applications, an appropriate sodium stearate content can be selected in accordance with the storage period, aiming to achieve precise storage goals. Therefore, the ethanol emitter has potential application prospects as an active packaging for Chinese bayberry fruit, as well as for other perishable products. © 2017 Society of Chemical Industry